1974
DOI: 10.1128/iai.10.4.948-956.1974
|View full text |Cite
|
Sign up to set email alerts
|

Habitat, Succession, Attachment, and Morphology of Segmented, Filamentous Microbes Indigenous to the Murine Gastrointestinal Tract

Abstract: Some indigenous microorganisms localize on epithelial surfaces in various areas of the digestive tracts of animals. One of these, a segmented, filamentous microbe, localizes on the epithelium in the small bowels of mice and rats. These filamentous microbes colonize mice at weaning time and persist in adult animals for at least 2 months. Results of the study of light and electron micrographs suggest that the microorganisms are procaryotic, and that they interact with small bowel epithelial cells to form an atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
125
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(139 citation statements)
references
References 17 publications
12
125
0
Order By: Relevance
“…This SFB was tentatively named Arthromitis (jointed thread), and similar morphotypes have been found in the chicken, rat, mouse, pig, and trout (Snel et al, 1995;Meyerholz et al, 2003;Yamauchi and Snel, 2000;Urdaci et al, 2001).The vertebrate versions of this morphotype are gram-positive, segmented, obligate anaerobes that are spore formers (Davis and Savage, 1974). Savage and coworkers recognized SFB as a major component of the gut microbiota of mice and were able to enrich for these noncultivatable bacteria by isolating intestinal epithelial cells, to which the 5-to 20-μm SFB attached firmly via a holdfast segment that interdigitated with but did not penetrate the brush border (Davis and Savage, 1974;Tannock et al, 1987). The SFB of mice has recently been isolated by the Nijmegen group, using treatment of fecal material with organic solvents to kill vegetative organisms, followed by limiting dilution to colonize formerly GF mice (Klaasen et al, 1991).…”
Section: Iga Plasma Cells and Effective Stimulators Among The Gut Micmentioning
confidence: 69%
See 2 more Smart Citations
“…This SFB was tentatively named Arthromitis (jointed thread), and similar morphotypes have been found in the chicken, rat, mouse, pig, and trout (Snel et al, 1995;Meyerholz et al, 2003;Yamauchi and Snel, 2000;Urdaci et al, 2001).The vertebrate versions of this morphotype are gram-positive, segmented, obligate anaerobes that are spore formers (Davis and Savage, 1974). Savage and coworkers recognized SFB as a major component of the gut microbiota of mice and were able to enrich for these noncultivatable bacteria by isolating intestinal epithelial cells, to which the 5-to 20-μm SFB attached firmly via a holdfast segment that interdigitated with but did not penetrate the brush border (Davis and Savage, 1974;Tannock et al, 1987). The SFB of mice has recently been isolated by the Nijmegen group, using treatment of fecal material with organic solvents to kill vegetative organisms, followed by limiting dilution to colonize formerly GF mice (Klaasen et al, 1991).…”
Section: Iga Plasma Cells and Effective Stimulators Among The Gut Micmentioning
confidence: 69%
“…These early studies have led to the development of mice with a defined intestinal flora-"altered Schaedler's flora"and these represent oligo-associated, gnotobiotic mice carrying eight benign commensal enteric bacteria (Dewhirst et al, 1999). Further definition of the normal intestinal microbiota of mice has led to discovery of a major colonizer, segmented filamentous bacteria (SFB) (Davis and Savage, 1974). These SFB have been shown to be related to clostridia (Snel et al, 1995), and variants have been found in rats, pigs, chickens, and trout (Snel et al, 1995;Meyerholz et al, 2002;Yamauchi and Snel, 2000;Urdaci et al, 2001).…”
Section: Interactions Of the Intestinal Microflora With The Host: Mammentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, however, only colonisation by the spore-enriched fraction of the mouse microbiota was Several clues led us to select SFB as a likely candidate. SFB are spore-forming Clostridia-related bacteria that colonise the mouse intestine at time of weaning concurrently to the initiation of the post-natal maturation of the gut immune barrier (Davis & Savage, 1974). SFB display tight adherence to ileal epithelial cells (Chase & Erlandsen, 1976;Davis & Savage, 1974;Ferguson & Birch-Andersen, 1979).…”
Section: Lessons From Colonisation Experiments In Gnotobiotic Micementioning
confidence: 99%
“…SFB are spore-forming Clostridia-related bacteria that colonise the mouse intestine at time of weaning concurrently to the initiation of the post-natal maturation of the gut immune barrier (Davis & Savage, 1974). SFB display tight adherence to ileal epithelial cells (Chase & Erlandsen, 1976;Davis & Savage, 1974;Ferguson & Birch-Andersen, 1979). Although SFB have been observed in many vertebrates, attachment has been shown to be species specific, suggesting that SFB species have coevolved with their respective hosts (Tannock, Miller, & Savage, 1984).…”
Section: Lessons From Colonisation Experiments In Gnotobiotic Micementioning
confidence: 99%